EVALUATION OF NAWAAT COVERAGE OF THE POLITICAL ASSASSINATIONS IN TUNISIA AFTER THE JASMINE REVOLUTION - SEBEI, Hatem (Linguagem: Estudos e Pesquisas, 2017)
This paper adopts a systemic functional linguistics as a paradigm to analyse postings on social media. This paradigmatic relationship is based on a combination of form and meaning. It adopts a Bakhtinian dialogic view of language and discourse. His viewpoint is built on the idea that every’s speaker voice is imbued with traces of previous voices and is in anticipation of other voices. This research shows how bloggers engage readers, how they negotiate and position themselves vis-à-vis the other voices. The current study adopts the Engagement framework as an analytical tool to evaluate the language used in Nawaat to cover the political assassinations in Tunisia. The current research focuses on the writer’s comments, description of the political assassinations. It also focuses on the writer’s comments, description and claims of external voices. Building solidarity and entente with readers who share and hold the same vision is also a matter of concern.